问题 解答题
脱式计算(能简算的要简算)
3
4
-
5
8
)÷(
1
2
-
1
3
1
4
×
1
4
+
3
4
×
1
4
60÷(3+
3
4
7
12
-
3
8
)×24-
5
9
5
24
+
7
12
-
2
3
)×48
1
3
÷
4
9
+
1
3
+
1
4
答案

(1)(

3
4
-
5
8
)÷(
1
2
-
1
3
),

=

1
8
÷
1
6

=

3
4

(2)

1
4
×
1
4
+
3
4
×
1
4

=

1
4
×(
1
4
+
3
4
),

=

1
4
×1,

=

1
4

(3)60÷(3+

3
4
),

=60÷3

3
4

=16;

(4)(

7
12
-
3
8
)×24-
5
9

=

7
12
×24-
3
8
×24-
5
9

=14-9-

5
9

=5-

5
9

=4

4
9

(5)(

5
24
+
7
12
-
2
3
)×48,

=

5
24
×48+
7
12
×48-
2
3
×48,

=10+28-32,

=38-32,

=6;

(6)

1
3
÷
4
9
+
1
3
+
1
4

=

3
4
+
1
4
+
1
3

=1+

1
3

=1

1
3

填空题
单项选择题